Model of success of the course workshop title certification in human medicine:publication of international impact: Modelo de éxito del curso taller de titulación por tesis en medicina humana: publicación de repercusión internacional - De La Cruz Vargas, Jhony Alberto (2019)
Promoting Research in Medical Students and increasing scientific production in the universities of Peru and Latin America is a priority and a necessity. It is an honor to share with you that we recently published in the prestigious journal Educación Medica, of Elsevier, indexed in Scopus, the scientific article that summarizes the experience and the success model of the Thesis Workshop Course that is given in the Faculty of Human Medicine of the Ricardo Palma University: Promoting research in medical students and increasing scientific production in universities: Experience of the Undergraduate Thesis Workshop Course.The undergraduate thesis represents academic work with scientific rigor, considered as the first serious step of university students in the field of research, which according to the new university law 30220 in force in Peru, is an essential requirement to obtain the university degree .   DOI:  10.25176/RFMH.v19.n1.1787